Evaluation and Strategic Enhancement of School Counselors' Accountability: A Qualitative Case Study Based on the M.E.A.S.U.R.E Framework at MTs Negeri in Bogor City - Putri Ria Angelina; Nurihsan, Juntika; Suherman, Uman; Yustiana, Yusi Riksa (Jurnal Pendidikan Islam, 2025)
Purpose – This study aims to evaluate the implementation of counselor accountability at MTs Negeri Kota Bogor and formulate evidence-based strategies to strengthen their professional practice. The research responds to systemic challenges in Indonesian public madrasahs, where high student-to-counselor ratios, limited facilities, and fragmented institutional support hinder effective counseling services aligned with national policy goals. Design/methods/approach – A qualitative intrinsic case study approach was employed, focusing on two key informants—a counselor and the school principal—through semi-structured interviews, direct observation, and document analysis. Thematic analysis was conducted using NVivo 12, guided by the M.E.A.S.U.R.E accountability framework (Dahir & Stone, 2003), with methodological triangulation and member checking to ensure credibility. Findings – Findings indicate that while the counselor applies systematic planning and evaluation procedures, accountability practices remain constrained by structural barriers. Notable initiatives include weekly documentation, digital-based student needs assessment, and collaborative service integration into classroom learning. However, ineffective communication with parents, insufficient training in data use, and the absence of specialized supervision impede sustainable accountability. Research implications – The findings support five actionable recommendations: (1) institutionalization of service-specific SOPs, (2) low-tech digital integration for reporting and assessment, (3) regular training in program evaluation and data utilization, (4) strengthened principal–counselor collaboration, and (5) strategic partnerships with external psychological service providers. These steps align with the goals of the Kurikulum Merdeka and Permendikbud No. 111/2014, and can inform national-scale policy refinements